Consumption of Fruits and Its Association with Nutritional Status in Chilean University Students Career of Physical Education [Consumo de Frutas y Su Asociación Con el Estado Nutricional en Estudiantes Universitarios Chilenos de la Carrera de Educación Física] - Herrera-Valenzuela, T (Grupo Aula Medica S.A., 2015)
Introduction: Chile is a country that reaches the highest levels of overweight and obesity worldwide (66.7% of the Chilean population), with a group of college students tending to swell these numbers considered nutritionally vulnerable group. Objective: To associate the consumption of fruits with nutritional status of Chilean university students in physical education. Methods: The study population consisted of all students of the School of Pedagogy in Physical Education from the Autonomous University of Chile, Temuco based (n = 420). The sample included 239 students (56.9%), men (76.5%) with a mean age of 21.5 ± 2.1 years. Each student nutritional status was determined and applied a validated survey eating habits. Results: An association between fruit consumption (≥2 servings ?day) in the model crude OR = 0.528 (from 0.288 to 0.965), Model 1 adjusted OR = 0.496 (0.268 to 0.916) and Model 2 adjusted OR = 0.495 is observed (0.265 to 0.924) Conclusion: Consumption ≥ 2 servings a day of fruits is a protective factor for a good BMI Chilean university students in physical education. © 2015 Grupo Aula Medica S.A. All rights reserved.